DEVELOPMENT OF ALGORITHMS AND PROGRAMS FOR PROCESSING SPEECH SIGNALS ON VISUAL DSP ++ PLATFORM (E Conference Zone, 2022)
Nowadays, digital signal processors or DSP (Digital Signal Processor) are very popular in the world and are even recognized as a separate field of science and technology. Analog Devices A practical guide to self-study and practical application of one of the digital signal processors. It contains a detailed description of the processor, schemes of its practical use and programming technology. At present, the growth of innovation activity, despite the importance of innovation in the field of management for the socio-economic development of society, is growing mainly due to technological innovation. The problems of effective introduction and dissemination of innovative management technologies in the field of information and communication have not yet been sufficiently studied. Little attention is paid to the study of world experience in the use of innovative technologies in the management of information and communication and the possibility of adapting it to the conditions of Uzbekistan. Insufficient theoretical and methodological development of this problem has determined the relevance of the chosen topic and the main directions of dissertation research